-''Mom, my friend's dad is a Serb''! –''Your mom is too, son'': War and national identification of children in early-90s Croatia - Grgurinović, Ivona; Marković, Jelena (2013)
The 1990s, during the war in Croatia, saw the affirmation of the so-called war ethnography, which focused on the poetics and politics of fear, death and resistance of war refugees from Croatia and Croat war refugees from Bosnia and Herzegovina. Very little of war ethnography research focused on children's experience of war, and the experiences of children – members of the Serb ethnic minority in Croatia or children from ethnically mixed families haven't to this day been the subject of cultural-anthropological and folkloristic research. It is often mentioned in everyday communication that people hadn't been aware of their neighbors' or parents', or even their own ethnicities. The focus of this paper are the personal narratives and anecdotes, that is, narratives of (un)mediated experience of now adult narrators, with ethnic Serb or ethnically mixed backgrounds and their experiences, and the experiences of their families, friends and acquaintances. The paper also focuses on coping strategies within the family in relation to the dominant nationalist political and public discourse at the time. The paper is based on oral testimonies of the shocking, unexpected revelation of their own parent's ethnic identity. The generations of children from the 1990s who grew up in environments that weren't directly affected by the war had their ''opportunity'' to imagine their national community in images of suffering, blood and horror, and frequently dealt with fear, shame and guilt, and provocations in school and in the street. This context has, among other things, made difficult the internalization of the identity of the Serb national minority in Croatia. On the one hand this was due to different parenting strategies of protection, understandable and justified conformism, and on the other to the fact that his generation has frequently felt the need to negate all forms of identity-forming national imagination. The mentioned personal narratives and anecdotes problematize the absence of a meaningful identificatory resource.
ENG